2019
DOI: 10.3389/fmicb.2019.01885
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genotypic Diversity Among Symbiotic and Non-symbiotic Bacteria Present in Chickpea Nodules in Morocco

Abstract: Environmental pollution problems and increased demand for green technologies in production are forcing farmers to introduce agricultural practices with a lower impact on the environment. Chickpea (Cicer arietinum) in arid and semi-arid environments is frequently affected by harsh environmental stresses such as heat, drought and salinity, which limit its growth and productivity and affect biological nitrogen fixation ability of rhizobia. Climate change had further aggravated these stresses. Inoculation with app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 95 publications
(139 reference statements)
2
11
0
Order By: Relevance
“…which can limit the development of rhizobia that prefer neutral or alkaline conditions during nodulation [ 63 ]. In addition, analysis of soil pH in Merchouch indicated that it is an acidic soil, and, therefore, we used acid tolerant rhizobia (MA72 and MA100; [ 9 ]) for inoculation to alleviate the effect of these produced acids during P solubilization.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…which can limit the development of rhizobia that prefer neutral or alkaline conditions during nodulation [ 63 ]. In addition, analysis of soil pH in Merchouch indicated that it is an acidic soil, and, therefore, we used acid tolerant rhizobia (MA72 and MA100; [ 9 ]) for inoculation to alleviate the effect of these produced acids during P solubilization.…”
Section: Discussionmentioning
confidence: 99%
“…The strains Mesorhizobium sp. MA72 and Mesorhizobium ciceri MA100 used in this study were isolated from chickpea nodules collected from chickpea fields in Morocco and characterized in our previous study [ 9 ]. They were tolerant to acidic pH 5.5–6.0 and other abiotic stresses (cold temperature of 4 °C, high temperature 36–40 °C, 513–684 mM of NaCl) and showed better symbiotic performance with chickpea [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations